Discussion on Geraghty Type Hybrid Contractions - Sara Salem Alzaid; Andreea Fulga; Fehaid Salem Alshammari (Journal of Function Spaces)
In this manuscript, we define the notion of Geraghty type hybrid contractions in the setting of b-metric spaces. We prove the existence of a fixed point for such mappings whenever b-metric space is complete. Our observed results not only unify several existing results but also extend some known results.